ARAH BARU MANAJEMEN PENDIDIKAN : DARI ADMINISTRASI KONVENSIONAL KE DIGITALISASI TOTAL - Ali Ramatni; Sophia Rahmi; Rini Dwi Septiyani; Nining Andriani; Ahmad Rudi Alpata; Wieke Tsanya Fariati (EDU RESEARCH, 2025)
The rapid development of digital technology has transformed various aspects of human life, including education management. This study discusses the shift from conventional administration to total digitalization in education management. The research aims to analyze the impact of digital transformation on efficiency, accessibility, and quality of educational administration. By utilizing qualitative methods, data were collected through literature studies and case studies of educational institutions that have implemented digital systems. The findings indicate that digitalization significantly improves administrative processes, reduces bureaucratic complexity, and enhances the responsiveness of educational institutions. However, challenges such as digital literacy, infrastructure readiness, and data security must be addressed for optimal implementation. This study contributes to the discourse on modern education management by providing insights into best practices and strategies for successful digital transformation. Future research is encouraged to explore the long-term impact of digital education management on learning outcomes and institutional performance.